Improving the K-12 Online Course Design Review Process: Experts Weigh in on iNACOL National Standards for Quality Online Courses - Adelstein, David; Barbour, Michael K. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2017)
Within the K-12 online learning environment there are a variety of standards that designers can utilize when creating online courses. To date, the only research-based standards available are proprietary in manner. As such, many jurisdictions have begun adopting online course design standards from the leading advocacy organization, which that have yet to be validated from a research perspective. This article reports on the second phase of a three-stage study designed to examine the validity and reliability of the iNACOL National Standards for Quality Online Courses. Phase two utilizes two groups of expert reviewers to examine and provide feedback with goal of further refining these standards (after the standards had been scrutinized through the lens of the available K-12 online learning literature).